Design of new controller for load frequency control of isolated microgrid considering system uncertainties. (2018) - Esmaeili, Mehran; Shayeghi, Hossein; Nooshyar, Mehdi; Aryanpour, Hamze
In this paper, a method for designing a load frequency control for micro grids after islanding has been proposed using neuro-fuzzy inference systems (ANFIS) control approaches. The three different controllers consisting optimal PID controller, fuzzy controller and a special kind of ANFIS controller have been compared. PID controller parameters are tuned using NSGA-II algorithm to minimise overshoot, settling time and integral square error over a wide-range of load changes. The PID controller parameters obtained from NSGA-II algorithm are used to train ANFIS. The performances of the controllers are implemented using MATLAB package. A comparison of ANFIS PID controller and other controllers indicates the superiority of proposed ANFIS-based approach over fuzzy PID and optimal PID controller for the same conditions.